Willingness to Pay for Satellite and Cable Television in Bangkok and Suburban Districts / ความยินดีที่จะจ่ายในการเลือกเป็นสมาชิกโทรทัศน์ดาวเทียมและเคเบิลทีวี ในเขตกรุงเทพมหานครและปริมณฑล - นันทนิตย์ ทองศรี, Nuntanid Thongsri / (Journal of Community Development Research (Humanities and Social Sciences), 2016)
บทคัดย่อ การศึกษาครั้งนี้มีจุดประสงค์เพื่อวิเคราะห์ปัจจัยที่มีอิทธิพลต่อการเลือกซื้อแพ็คเกจโทรทัศน์ดาวเทียมและเคเบิลทีวีแบบจ่ายรายเดือน และประเมินค่าความยินดีที่จะจ่ายของผู้บริโภค โดยใช้วิธีการทดลองทางเลือก (Choice Experiment) โดยในแต่ละทางเลือกนั้นประกอบ ไปด้วยคุณลักษณะของแพ็คเกจแบบรายเดือนของโทรทัศน์ดาวเทียมและเคเบิลทีวีในแต่ละระดับและราคาของแพ็คเกจในทางเลือกนั้นๆแตกต่างกัน ซึ่งได้เก็บข้อมูลปฐมภูมิจากการสัมภาษณ์ผู้บริโภคกลุ่มตัวอย่าง ในเขตกรุงเทพมหานครและปริมณฑลจำนวน 507 ราย จากการวิเคราะห์อรรถประโยชน์ทางอ้อมของผู้บริโภคที่ได้จากการตัดสินใจเลือกแพ็คเกจภายใต้สถานการณ์ที่มีชุดของคุณลักษณะของแพ็คเกจในระดับที่แตกต่างกันโดยใช้แบบจำลอง Conditional Logit พบว่า ปัจจัยที่มีผลต่อการเลือกซื้อแพ็คเกจของกลุ่มตัวอย่างมากที่สุด คือ บริการเสริมที่รวมอยู่ในแพ็คเกจ (การรวมค่าบริการติดตั้ง, การรวมอินเทอร์เน็ตคุณภาพสูง และการรวมค่าโทรศัพท์บ้าน/เคลื่อนที่) รองลงมา คือ คุณภาพสัญญาณ, รายการฟุตบอล, รายการภาพยนตร์/ซีรี่ย์ และรายการทั่วไป (บันเทิง, สารคดี, ข่าวต่างประเทศ)   ในส่วนของความยินดีที่จะจ่ายกลุ่มตัวอย่างมีความยินดีที่จะจ่ายให้กับรายการฟุตบอลยุโรปมากที่สุด รองลงมา คือ รายการฟุตบอลไทย การรวมบริการอินเทอร์เน็ตคุณภาพสูง คุณภาพสัญญาณความคมชัดสูง ซีรี่ย์ต่างประเทศ ภาพยนตร์ต่างประเทศ และรายการบันเทิง/ วาไรตี้ ตามลำดับ นอกจากนั้นแล้วจำนวนเงินของความยินดีที่จะจ่ายยังแตกต่างกันไปตามเพศ สถานะ รายได้ และประสบการณ์การติดตั้งเคเบิลทีวี/ดาวเทียม เป็นต้น   คำสำคัญ : วิธีการทดลองทางเลือก  ความยินดีที่จะจ่าย   Abstract This research aims to identify factors determining consumer preferences and willingness to pay of attributes in Cable televisions’ package in Bangkok and Suburban Districts, Thailand. The Choice Experiment Method was employed in finding factors affecting and willingness to pay in each alternative that consist of the difference in level of attribute and price of Cable televisions’ package. The primary data for the study were gathered by face-to-face interview from 507 samples in Bangkok and Suburban Districts. The analyzed indirect utility function of consumers when selected the package that has different level in each attribute. Conditional logit models comprising package attributes were estimated for all samples and various sub-samples regarding individuals’ socio-demographic characteristics such as gender, monthly income, status, and adopting experience in cable television. The results found additional service (offering setup setting, offering hi-speed internet, offering fixed-line telephone) is the most importance characteristic that affecting the package purchasing decision, follow by video quality, football content, movies and series content, and general content (i.e. entertainment, documentary, news) respectively. The models were then used to compute the marginal willingness to pay for each attribute levels. The result showed that the consumers willing to pay more if the attribute is football content, offering hi-speed internet, video quality (high definition), series, movies, and entertainment respectively. Keywords: Choice Experiment, Willingness to Pay
Keywords: วิธีการทดลองทางเลือก ความยินดีที่จะจ่าย Choice Experiment, Willingness to Pay